Modern studies world powers and international issues - Cooney, Frank; Hughes, Gary; Kelly, Pauline (Dynamic learning, 2019)
Exam Board: SQA Level: National 5 Subject: Modern Studies First Teaching: September 2017 First Exam: Summer 2018 This second edition comprehensively covers the changes made to the course content and prepares students to cope with the increased emphasis on knowledge and understanding in the new National 5 exam. - Analyses the USA, China and South Africa - Covers Development Issues in Africa and International Terrorism in depth.